2020
DOI: 10.3390/ijms21218188
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Damage in Biomolecules and Cells

Abstract: Ionizing radiation is widely used in medicine, both as a diagnostic tool and as a therapeutic agent [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This detector's sheet was cut into small pieces (1cm 2 areas each). It is encased in plastic on both sides, and this plastic is removed when it is used to protect it from radiological background 2 . Because of its sensitivity, such a detector can detect alphas tracks at low energy levels 15 .…”
Section: Urinementioning
confidence: 99%
See 2 more Smart Citations
“…This detector's sheet was cut into small pieces (1cm 2 areas each). It is encased in plastic on both sides, and this plastic is removed when it is used to protect it from radiological background 2 . Because of its sensitivity, such a detector can detect alphas tracks at low energy levels 15 .…”
Section: Urinementioning
confidence: 99%
“…Human exposes to ionizing radiation from natural sources and sometimes from synthetic sources that come from human activities. The dangerous effect of ionizing radiation is the biological damage to Deoxyribonucleic Acid (DNA) or another part of the body 2 . The Types of radiation that effects human health is alpha, beta, gamma, neutron, and gamma rays, and each radiation has different properties 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, numerous studies have reported genetic damage produced by ionizing radiation ( Carante and Ballarini, 2020 ; Beheshti et al, 2021 ; Cornforth et al, 2021 ). Ionizing radiation can affect nucleic acids, proteins, and complex lipids either by direct deposition of energy into macromolecules or by generating reactive oxygen species (ROS) including hydrogen peroxide, superoxide anions, and other free radicals ( Azzam et al, 2012 ; Selim et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%